Genetic transformation of bean callus via Agrobacterium- mediated DNA transfer - Eissa Ahmed, E. (International Journal of Horticultural Science, 2003)
Callus cultures were induced from hypocotyl of young bean seedlings. Callus developed and maintenaned on B5 medium supplemented with 2mg/1 2,4-D and 1 mg/1 kinetin. The results demonstrate that A. tumefacins-mediated transformation is a convenient method to obtain transient gene expression in callus of bean. The results have shown that the bean callus co-cultivated with A. tumefaciens can be transformed to get heibicide Finale (glufosinate-ammonium) resistant GUS positive tissues. Southern blot analysis of transformed calli showed integration of gusA marker gene carried by a binary vector. Transformed calli were selected on herbicide containing media. Data of molecular analysis (Southern blotting) confirmed the insertion of gusA gene in the genome of herbicide resistant calli with bar gene. There are three evidences that calli are stable transformants: (1) herbicide resistance, (2) GUS activity which is indicative since the coding region containing an intron, (3) the results of Southern hybridization technique.